2021
DOI: 10.3390/ani11113308
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Death in Stray Cat Colonies of Milan: A Five-Year Report

Abstract: The presence of cats in urban environments has a long history. In Italy, stray cats are protected by national and regional laws, and programs of neutering and reintroduction to colonies are ongoing. Colony cats have been widely studied from a behavioral perspective, while surveys regarding their causes of death are limited, although they may provide relevant information related to public health and cat welfare. This retrospective study provides pathological descriptions and statistical analyses of the causes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…This finding might be justified by the behavioral habits of these cats; indeed, compared to the other sex categories, intact males are less likely to settle down in a defined territory and tend to roam in search of resources or females for mating [ 25 ]. These movements expose them to the possibility of being traumatized by road traffic accidents or to bite wounds injuries [ 6 , 9 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding might be justified by the behavioral habits of these cats; indeed, compared to the other sex categories, intact males are less likely to settle down in a defined territory and tend to roam in search of resources or females for mating [ 25 ]. These movements expose them to the possibility of being traumatized by road traffic accidents or to bite wounds injuries [ 6 , 9 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a higher risk of dying has been reported in sheltered kittens with lighter body weight, with low BCS, and those diagnosed with panleukopenia [ 17 ]. Moreover, it has been previously reported that panleukopenia is a common cause of mortality in kittens and young cats [ 6 ], both among unowned and owned feline patients [ 38 ]. Whereas a multi-patient environment, such as during hospitalization or sheltering, and an incomplete or absent vaccination protocol has been demonstrated a predisposing factor for the development of panleukopenia [ 39 ]; we supposed that death of these patients from feline panleukopenia should not be considered entirely independent from the traumatic event.…”
Section: Discussionmentioning
confidence: 99%
“…In a study looking at causes of death in cats living in free roaming colonies in the city of Milan, Italy the most common causes of death included inflammatory diseases (which included infectious causes), organ failure and trauma [ 14 ]. It is not surprising that the results in this study differed given that these animals were unowned and faced different pressures than owned cats.…”
Section: Discussionmentioning
confidence: 99%
“…In the U.S., early estimates suggest there may be more than 30 million free-ranging feral/stray cats (31). Feral/stray cats often live in large groups (known as feral cat colonies) in which some viruses are highly prevalent (32)and large-scale outbreaks can occur (33). In many cities in the U.S., including New York City (NYC), humans often provide food for stray cats through feeding stations.…”
Section: Introductionmentioning
confidence: 99%